"Knowledge Will Be Manifold": Daniel 12.4 and the Idea of Intellectual Progress in the Middle Ages. Issue 2 (9th April 2014) - Webb, J. R.
<x content-type="archive" xml:space="preserve">Abstract</x> Thus wrote Michelet to open his monumental history of France. By deploying this prophetic line from the book of Daniel in support of a positivistic approach to historical science, he was participating in a discourse on this perplexing passage that spanned nearly two millennia. He perhaps surmised this, though he probably did not know how deeply the passage penetrated into the intellectual tradition of the West or that he was favoring one interpretation of it over another. It is the trajectory of the interpretations of Daniel 12.4 in the Latin West from their first formulation in late antiquity that concerns the present exploration.